FUNCTIONAL OUTCOME OF PATIENTS WITH MODERATE-TO-SEVERE MEDIAL COMPARTMENT OSTEOARTHRITIS KNEE TREATED BY HIGH TIBIAL OSTEOTOMY AT A TERTIARY CARE CENTER - RAJESH KUMAR KANOJI; HIMANSHU; PRADEEP KUMAR SUTHAR (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: (1) The aims and objectives of the study are to assess functional outcomes in knee osteoarthritis (OA) cases treated by high tibial osteotomy (HTO) and (2) to study the complications in patients undergoing HTO. Methods: This was a prospective study conducted in the Department of Orthopedics of a tertiary care medical college. 50 patients with moderate-to-severe OA of medial compartment of knee were included in this study. All patients underwent HTO. Post-operatively, patients were followed up for 6 months. During follow-up visits, reduction in pain intensity and functional outcome were assessed by visual analog scale (VAS) score and Japanese Orthopedic Association (JOA) Score. Patients were also assessed for complications if any. For statistical purposes, p<0.05 was taken as statistically significant. Results: Out of 50 studied cases, there was a female preponderance with an M: F ratio of 1:1.38. The mean age of affected cases was found to be 62.32±8.94 years. 11 (22.00%) patients were obese (body mass index [BMI] ≥30) and 32 (64.00%) patients were overweight (BMI ≥25 but <30). 7 (14.00%) patients had BMI <25. 38 (76%) patients had severe OA whereas in remaining 12 (24%) patients, there was moderate OA. There was a significant reduction in pain, as assessed by VAS score, at the time of final follow-up as compared to VAS score at the time of presentation (p<0.0001). Similarly, there was a significant functional improvement, as assessed by JOA score, at the time of final follow-up as compared to JOA score at the time of presentation (p<0.0001). 7 (14%) patients developed minor complications. All these complications were managed conservatively. Conclusion: Patients with moderate to severe OA of medial compartment of knee treated by HTO show excellent outcomes in terms of pain relief and functional outcomes.